THE UNBORN ONE - Ram, S. Sri (SCHOOL SCIENCE, 2013)
I have seen hundreds of eggs, yet never have I been able to look through the shell and perceive the wonder within, never have I been able to appreciate the extraordinary genius of Nature hidden inside the wonderful egg. How does young chick, full of life, emerge from an egg, which to all appearance was a mere bit of sticky yolk? I could only find out by examining eggs of various ages. The purpose of this project was to study the chick’s development while still in the egg. I knew that that there was something that happened in the egg when a hen sat on it, and perhaps that is how a chick is formed from the egg.